GENDER FEATURES OF STUDENTS’ EMOTIONAL STATES DURING UNIVERSITY LECTURES - Hrytsuk, Oksana (PSYCHOLOGICAL JOURNAL, 2020)
The article describes the empirical study of gender features of students’ emotional states during university lectures. The parameters assessing the manifestations of students’ emotional states were selected and substantiated. We used the following parameters for assessment of students’ emotional states during lectures: 1) well-being, psycho-emotional reactions to mental stress, general mental state; 2) activity, mobility, speed of mental functions; 3) mood, the emotional background of physiological and mental functions. The peculiarities of students’ emotional states were assessed with the method of “Well-being, Activity, Mood” (V.O. Doskin, N.O. Lavrentyeva, V.B. Sharay, M.P. Miroshnikov). The sample consisted of 193 students from Ukrainian universities of the I-VI academic years: 24 students of the I academic year (9 women, 15 men), 45 students of the II academic year (18 women, 27 men), 23 students of the III academic year (9 women, 14 men), 48 students of the IV academic year (20 women, 28 men), 33 student of the V academic year (18 women, 15 men), 20 student of the VI - academic years (11 women, 9 men). The obtained data were processed by STATISTICA 12 package. The t-test for independent samples was used to compare two samples (male and female students). The comparison of the mean values with t-test was evaluated for significance, thus the statistical reliability of an existing difference between the means was estimated. We found that the boys of the I, V and VI academic years showed quite similar values for the scales of “well-being”, “activity”, and “mood”. They had positive emotional state, so that they could perform their tasks efficiently. The girls of all academic years showed low indicators of well-being and activity and medium mood indicators; they were not able to take a break from their main activity and used all their strength to university study. The prospect of further explorations in this direction is to analyze gender characteristics of students’ emotional states during seminars, comparing them with their states during lectures.